(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Cognitive impairment is a common adverse effect associated with carbamazepine use. One of the proposed mechanisms for cognitive impairment may be attributed to the pro-oxidant properties of carbamazepine. This study investigated the effects of L-Arginine supplementation with carbamazepine on cognition in adult male non-epileptic rats. Adult male Sprague-Dawley rats with average weight 200g to 220g were divided into 4 groups; (1) Control group treated with distilled water, (2) L-Arginine group treated with L-Arginine (100mg/kg BW) in distilled water, (3) Carbamazepine group treated with carbamazepine (25mg/kg BW twice daily) in distilled water, and (4) Carbamazepine + L-Arginine group treated with Carbamazepine and L-Arginine as above for two weeks to assess the acute changes in cognition and oxidative stress markers. Following two weeks of treatment, cognition was assessed using the Y-maze, after which the rats were humanely sacrificed with the hippocampus and frontal lobes isolated from the brain and subsequently homogenized for assessment of oxidative stress markers [(Catalase, superoxide dismutase (SOD), malondialdehyde (MDA), and reduced Glutathione (GSH)]. Arm entry and correct alternation were significantly higher (p < 0.05) in the L-Arginine and L-Arginine + Carbamazepine groups compared to carbamazepine group. In the frontal lobe, L-Arginine significantly increased (p < 0.05) catalase and GSH levels compared to other groups while in the hippocampus, it significantly (p < 0.05) reduced MDA with no change in other parameters. Likewise, SOD and MDA levels were significantly lower (p < 0.05) in the L-Arginine + Carbamazepine group compared to other groups. Oral L-Arginine supplementation with carbamazepine improved cognitive performance on Y maze.